Main Factors of Competitiveness and Growth after Credit Crunch with the Focus on Asia - Jałowiecki, Marcin (Główne czynniki konkurencyjności i wzrostu po kryzysie kredytowym na rynku Azjatyckim, 2010)
The article describes key factors for governments and courtiers of competitiveness and growth after credit crunch in USA with the focus on Asia. The crisis has raised some fundamental questions about the sustainability of the export-led approach to growth, given debt and unemployment levels in Asia's traditional export markets, and the increased likelihood of Asian currency appreciation reducing the competitiveness of the region's exports. The Asian economies have performed relatively well during the first global recession since World War II. This performance was partially a result of Asian governments' fiscal and monetary stimulus packages that offset the falloff in Asian exports to markets such as North America and Europe.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 121-131
Keywords: Asia; growth factors; global financial crisis; global capital market